Letter from C. W. Johnson to James Curtis Booth - Johnson, C. W. (1860)
C. W. Johnson, seeking employment, writes to James Curtis Booth (1810-1888) to see if there is any "employment in your laboratory attainable by a young man of twenty-five 'with satisfactory recommendation'."
Keywords: Booth, James Curtis, 1810-1888; Chemistry teachers; Laboratories